Effect of HER2-low expression on the efficacy of neoadjuvant chemotherapy in triple-negative breast cancer - Lin-Yu Xia; Xu-Chen Cao; Yue Yu (Scientific Reports)
Abstract It is reported that HER2-low breast cancer (BC) demonstrates a poor response to neoadjuvant chemotherapy (NACT), whereas the response and impact of HER2-low triple-negative breast cancer (TNBC) to NACT remain controversial. TNBC patients who received standard NACT at Tianjin Medical University Cancer Hospital were retrospectively enrolled. The pathological complete response (pCR) rate of NACT were compared between HER2-low and HER2-zero patients. Logistic regression analyses were performed to identify the independent factors affecting the pCR rate in patients with HER2-low TNBC after NACT. We finally included 369 HER2-low and 245 HER2-zero patients with TNBC. The axillary lymph nodes pathological complete response (npCR) rate and total pathological complete response (tpCR) rate after NACT in the HER2-low group were worse than that in the HER2-zero group, and there was no statistical difference in breast pathological complete response (bpCR) between the two groups. In HER2-low TNBC patients, multivariate analysis showed that early clinical lymph node stage, high Ki67 expression, use of immunotherapy and bpCR were independent influencing factors for npCR. Premenopause, small clinical tumor size, early clinical lymph node stage, CK5/6 positivity and EGFR negativity were independent factors affecting tpCR. The npCR and tpCR of HER2-low TNBC patients are worse than those of HER2-zero TNBC patients.